New Nakhichevan Dialect as an Element of the Armenian National Identity - Botsinyan, Mariana (Տիգրան Մեծ)
The formation of the Armenian Diaspora was specifically crucial for the Armenian people and the Ar-menian language. Armenians worldwide have expanded the range of the Armenian language, exerting great efforts to preserve the integrity of the language. Conditioned by this, one noticeable problem for the literary language has emerged; as much as foreignisms are dangerous for the language, purisms are equal-ly dangerous.The article is dedicated to one of the critical elements of self-determination of Armenians living in the region of New Nakhichevan; the current language status of the Armenian dialect, the scope of its use and the preservation of the national face through language. In order to avoid the danger of assimilation, especially the representatives of the Western dialect group create Armenian morphemesand try to translate all the words indiscriminately, even internationally ac-ceptable terms, which signals the fear living in the subconscious that the distortion of the language will lead to the distortion of the national identity. Dialects also evincefeaturesin semantics. In the article, we have presented several words used in the dialect, which, compared to other Armenian dialects, coincide in terms of expression but differ in terms of content.
Keywords: Philosophy of education